Two‐year follow‐up of a primary care‐based intervention to prevent and manage childhood obesity: the High Five for Kids study. Issue 3 (27th May 2016) - Rifas‐Shiman, Sheryl L.; Taveras, Elsie M.; Gortmaker, Steven L.; Hohman, Katherine H.; Horan, Christine M.; Kleinman, Ken P.; Mitchell, Kathleen; Price, Sarah; Prosser, Lisa A.; Gillman, Matthew W.
Summary: Background: The obesity epidemic has spared no age group, even young infants. Most childhood obesity is incident by the age of 5 years, making prevention in preschool years a priority. Objective: To examine 2‐year changes in age‐ and sex‐specific BMI z ‐scores and obesity‐related behaviours among 441 of the 475 originally recruited participants in High Five for Kids, a cluster randomized controlled trial in 10 paediatric practices. Methods: The intervention included a more intensive 1‐year intervention period (four in‐person visits and two phone calls) followed by a less intensive 1‐year maintenance period (two in‐person visits) among children who were overweight or obese and age 2–6 years at enrolment. The five intervention practices restructured care to manage these children including motivational interviewing and educational modules targeting television viewing and intakes of fast food and sugar‐sweetened beverages. Results: After 2 years, compared with usual care, intervention participants had similar changes in BMI z ‐scores (−0.04 units; 95% CI −0.14, 0.06), television viewing (−0.20 h/d; −0.49 to 0.09) and intakes of fast food (−0.09 servings/week; −0.34 to 0.17) and sugar‐sweetened beverages (−0.26 servings/day; −0.67 to 0.14). Conclusion: High Five for Kids, a primarily clinical‐based intervention, did not affect BMI z ‐scores or obesity‐related behaviours after 2 years.